การผลิตไฮโดรจิเนเตดไบโอดีเซลด้วยปฏิกิริยาไฮโดรจิเนชันบางส่วนแบบต่อเนื่องโดยใช้ตัวเร่งปฏิกิริยานิกเกิล - ศุภณัฐ พุ่มประดิษฐ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The partial hydrogenation fatty acid methyl ester (FAME) derived from palm oil catalyzed was examined by using nickel (Ni) catalysts supported on two type of silica: commercial silica ball (SB) and silica fiber (SF) in a continuous fixed-bed reactor in temperature range of 100-250 °C under hydrogen atmosphere at 1-4 bar with FAME flow rate of 0.3-0.7 mL/min. Since the composition in FAME was consisted of methyl linolenate (C18:3) and methyl linoleate (C18:2) having poor oxidation stability, the methyl oleate (cis-C18:1) was desired due to its balance in term of oxidation stability and cold flow properties. The results showed that Ni/SB and Ni/SF catalyst had reduction temperature of nikel oxide (NiO) in range of 350-450 °C. It was observed that the H2 consumption and reducibility of Ni/SF catalyst was higher Ni/SB catalyst indicating that the Ni/SF catalyst had higher hydrogenation activity, due to the lower mass transfer limitation than porous catalysts. Moreover, the use of the 30%Ni/SF catalyst at 200 °C under 1 bar H2 pressure and the FAME floe rate of 0.5 mL/min provided C18:2 conversion and cis-C18:1 selectivity at 71% and 41%, respectively. However, the methyl elaidate (trans-C18:1) was found as 3%. This was equal that of the Ni/SB catalyst system at the same reaction condition as 3%. When the spent Ni/SF catalyst was regeneration for 5 times, the hydrogenation activity of this catalyst was decrease 28% possible due to the sintering effect of Ni particles or the loss of Ni particle.